Sistem Informasi Rektrutmen Calon Perangkat Desa sebagai Ruang Partisipasi Warga dan Pemerintah Desa Cangkring Rembang Karanganyar Demak - nurkamid, mukhamad - (Jurnal Transformatika, 2019)
he purpose of this research is to find out the description of the prospective village apparatus recruitment system applied to the Cangkring Rembang village government system, to analyze the recruitment system of village apparatuses that are applied for system development in the form of web-based candidate village recruitment information system design. This research was conducted in the village of Cangkring Rembang, Karanganyar District, Demak. Cangkring Rembang Demak village government in carrying out its duties, principal and government functions is one of them is the process of recruiting prospective village officials is still done manually. With manual systems documents can be lost, damaged and stored in several different storage spaces. In addition, the verification process for prospective applicant data takes a long time. Another disadvantage, if the document is needed at any time for public publication needs is not recorded properly so that it can not be used as decision making quickly. The application development method uses the waterfall approach. The results of this study are a system of recruiting prospective village officials who can provide alternatives (solutions) for prospective applicants, especially in the process of recruiting prospective village officials. With the development of a web system, in addition to documents, it is easier to store in the online storage space, organizing recruitment of prospective village officials can run transparently and participatively. A participatory government system shows open governance, one of which is by providing various information that can be accessed by every citizen